Sex differences in hypothalamic-mediated tonic norepinephrine release for thermal hyperalgesia in rats. (2nd June 2016) - Wagner, M.; Banerjee, T.; Jeong, Y.; Holden, J.E.
Highlights: Tonic release of norepinephrine was pronociceptive at α1 -adrenoceptors. Antinociception from α2 -adrenoceptors was not observed. No sex difference was seen after blockade of A7 catecholamine cell group. Sex differences occurred in hypothalamic-mediated tonic norepinephrine release. Abstract: Neuropathic pain is treated using serotonin norepinephrine reuptake inhibitors with mixed results. Pain facilitation mediated by α1 -adrenoceptors may be involved, but whether norepinephrine (NE) is tonically released is unclear. The aim of this study was to determine whether NE is tonically released from A7 cells following chronic constriction injury (CCI), and if the lateral hypothalamus (LH) plays a role in this release in male and female rats with nociceptive and neuropathic pain types. Neuropathic groups received left CCI while nociceptive groups remained naïve to injury. Fourteen days later, rats were given intrathecal infusion of either the α1 -adrenoceptor antagonist WB4101, the α2 -adrenoceptor antagonist yohimbine (74 μg), or normal saline for control. Paw withdrawal latency (PWL) from a thermal stimulus was measured. The generalized estimated equation method was used for statistical analysis. Nociceptive rats given WB4101 had a PWL significantly longer than saline control (7.89 ± 0.63 vs. 5.87 ± 0.52 s), while the PWL of neuropathic rats given WB4101 was 13.20 ± 0.52 s compared to 6.78 ± 0.52 s for the saline control rats. Yohimbine had no significant effect. Microinjection of cobalt chloride (CoCl) in the A7 catecholamine cell group to prevent synaptic transmission blocked the effect of WB4101 in all groups, supporting the notion that spinally descending A7 cells tonically release NE that contributes to α1 -mediated nociceptive facilitation. Microinjection of CoCl into the left LH blocked the effect of WB4101 in nociceptive and neuropathic male rats, but had no effect in female rats of either pain type, suggesting differential innervation. These findings indicate that tonic release of NE acts at pronociceptive α1 -adrenoceptors, that this effect is greater in rats with nerve damage, and that, while NE comes primarily from the A7 cell group, LH innervation of the A7 cell group is different between the sexes.